PEMBINAAN PEMANFAATAN LIMBAH BOTOL PLASTIK UNTUK MEDIA PEMBELAJARAN IPA INTERAKTIF - Sudiman, Sudiman; Sewaka, Sewaka; Ibnu S., Fredy Dwi; Pitono, Wuguh; Anwar, Andri Khairul (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
In the industrial world, competence in conducting industrial processes is very important to support independence in developing industry in society. Empowering teacher and student guardians conducted at MI Nurul Iman Cisauk Tangerang, this activity was carried out in an effort to increase competence and independence in conducting industrial activities. The purpose of this activity is to train and foster the competence of MI Nurul Iman's teacher and guardians for entrepreneurship by using leisure time outside of routine activities. To achieve this goal, the community service team of the Industrial Engineering Study Program has provided counseling, training and assistance to MI Nurul Iman's teaching staff and parents in producing dish soap. Teachers and guardians of students are given knowledge about the swift industrial competition, so competence in conducting industrial processes must be owned and developed in the community environment. Teachers and student guardians are also given training on how to make dish soap, as well as product packaging and marketing techniques.